Performance study of direction of arrival (DOA) estimation algorithms for linear array antenna - Islam, Md. Rafiqul; Adam, Ibrahim A. H. (2009)
This paper presents the performance analysis of five direction of arrival estimation algorithms namely Bartlett, Minimum Variance Distortionless Response (MVDR), Linear Prediction and MUSIC DOA Estimates. We present the description, comparison and the performance and resolution analyses of these algorithms. Sensitivity to various perturbations and the effect of parameters related to the design of the sensor array itself such as the number of array elements and their spacing are also investigated. The analysis is based on linear array antenna and the calculation of the pseudospectra function of the estimation algorithms. Matlab is used for simulating the algorithms.